Enhancing the engine performance using multi fruits peel (exocarp) ash with nanoparticles in biodiesel production. Issue 1 (31st December 2023) - Thanikodi, Sathish; Milano, Jassinnee; Sebayang, Abdi Hanra; Shamsuddin, Abd Halim; Rangappa, Sanjay Mavinkere; Siengchin, Suchart; Silitonga, Arridina Susan; Bahar, Aditiya Harjon; Ibrahim, Husin; Benu, Siti Maretia
ABSTRACT: The increase of motor vehicles results in a rapid increase in fuel supply and generates high emissions, which then affects the environment and human health in general. Replacement of nonrenewable fuels can be achieved by using alternative energy sources. Viewing fuel properties and production routes, biodiesel is deemed as one preferred alternative fuel for diesel engines. This work focuses on biodiesel production using waste cooking oil through a catalyst made of mixed multi-fruits' peel ash and titanium dioxide nanoparticles through a transesterification process. Further, the produced biodiesel was used to evaluate the engine performance by analyzing brake thermal efficiency and brake-specific fuel consumption. Emission characteristics due to biodiesel combustion, namely carbon monoxide and nitrogen oxides, was our main focus in this study. Both engine performance and emissions levels were optimized through Taguchi L16 orthogonal array. Highest brake thermal efficiency of 36.19% was achieved by the influence of 450°C of calcination temperature, 30°C of reaction temperature, 4% of catalyst loading, and 3 hr time of reaction. The lowest brake-specific fuel consumption obtained is 0.23 kg/kWh by involving 300°C of calcination temperature, 60°C of reaction temperature, 4% of catalyst loading, and 5 hr time. The statistical analysis based on ANOVA shows that the studied parameters does contribute to the developed regression model. In emission analysis, calcination temperature greatly influenced both CO and NOx .